The Impact Of Interest Rate, Inflation, Earnings Per Share, And Return On Asset On Stock Price In Banking Subsector Companies Listed On The Indonesia Stock Exchange 2019-2022 - Simanjuntak, Jessica Maranatha; Khairunnisa, Khairunnisa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Generally, investors preferred companies with large market capitalization to minimize risks, such as banking companies. The occurrence of Covid-19 has negatively impacted the macro and microeconomics. This research aimed to investigate whether macroeconomic and microeconomic factors (company performance) influenced the stock prices of banking companies from 2019 to 2022. The research employs multiple linear regression as its methodology. Based on the research findings, interest rates, inflation, earnings per share, and return on assets collectively influence the stock prices of banking institutions. However, in partial analysis, interest rates, inflation, and return on assets do not have a significant impact on the stock prices of banking institutions, whereas earnings per share does have a significant influence./